The Relevance of Implementing a Holistic Curriculum with Holistic Peer Parenting in Early Childhood Education - Sri Widaningsih (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The growth and development of Early Childhood (EC) is holistic. Thus, the development process requires facilities to help it, the implementation of the curriculum and parenting patterns in the learning process must also be able to be holistic and comprehensive. This research aims to see the relevance of the curriculum to holistic peer parenting in early childhood education research, the method used is grounded theory, systematic design, data collection techniques and the development of instruments used in this research is through cross-checked observations with an interview process. with teachers, and document analysis. The analysis technique is a cycle consisting of; data collection, coding, axial coding, selective coding, and conventional coding. The results of this research are that the implementation of the existing curriculum in the field is very relevant to the holistic parenting pattern of peers because peer parenting is directly integrated into the curriculum/learning implementation process, where both can develop all of the child's basic potential such as intellectual, physical, spiritual, emotional, social and aesthetic), as well as the relationship between the individual and other people, the individual and natural environment, the student's self and the external maximally and completely. However, in the process, the teacher must be able to help, guide, and direct so that the process can achieve all the achievements in the curriculum.